Ilustrar poesia para a infância: entre as rimas cromáticas e as metáforas visuais - Ana Margarida Ramos (Ocnos, 2014)
This paper identifies a corpus of anthologies of children’s poetry published in Portugal in last few years where illustration plays an important role in assuring the cohesion of the volumes and in the reading process of the texts. The paper also analyses the relationships established between images and texts in order to understand the specificity of children’s poetry illustration, identifying illustration functions and particular strategies that link text and image.